Effect of Diet and Water Intake on Aquaporin 2 Function - Jun-Mo Kim; Tae-Hee Kim; Tong Wang (Korean Society of Pediatric Nephrology, 2016)
Appropriate control of diet and water intake is important for maintaining normal blood pressure, fluid and electrolyte homeostasis in the body. It is relatively understood that the amount of sodium and potassium intake directly affects blood pressure and regulates ion transporters; Na and K channel functions in the kidney. However, little is known about whether diet and water intake regulates Aquaporin (AQP) function. AQPs, a family of aquaporin proteins with different types being expressed in different tissues, are important for water absorption by the cell. Water reabsorption is a passive process driven by osmotic gradient and water permeability is critical for this process. In most of the nephron, however, water reabsorption is unregulated and coupled to solute reabsorption, such as AQP1 mediated water absorption in the proximal tubule. AQP2 is the only water channel founded so far that can be regulated by hormones in the kidney. AQP2 expressed in the apical membrane of the principal cells in the collecting tubule can be regulated by vasopressin (antidiuretic hormone) controlling the final volume of urine excretion. When vasopressin binds to its receptor on the collecting duct cells, it stimulates the translocation of AQP2 to the membrane, leading to increased water absorption via this AQP2 water channel. However, some studies also indicated that the AQP2 is also been regulated by vasopressin independent mechanism. This review is focused on the regulation of AQP2 by diet and the amount of water intake on salt and water homeostasis.